Resource Management in Local Governments: A Bane or a Boon to Development at the Local Level in Ghana - Anthony Aikins; John Mensah; Augustina Amissah (International Journal of Management, Accounting and Economics)
The decentralised local government system makes funds available to local governments to develop the communities and improve living conditions of the people. In Ghana, however, the people in the communities complain of poor service delivery including the provision of poor amenities. This deprives them of decent livelihood and there is despondency at the local level. This study investigated the situation by examining the operations of local governments to ascertain the management of resources at the local level. Using the transaction cost theory and the institutional theory, desk research was conducted based on successive Auditor-Generals’ reports and other relevant documents on local governance in Ghana. The data were subjected to thematic analysis for interpretation and comparison. The study found that the local governments performed their basic functions but successive Auditor-Generals’ reports contained irregularities which were the result of mismanagement of resources. The management of resources in local governments is, therefore, a bane rather than a boon to development at the local level in Ghana. The Head of Local Government Service should severely sanction perpetrators of irregularities.